2008
DOI: 10.1029/2007jf000789
|View full text |Cite
|
Sign up to set email alerts
|

Aspect‐related microclimatic influences on slope forms and processes, northeastern Arizona

Abstract: [1] Climate is a major control on geomorphology, yet the effects of aspect-related differences in microclimate have been little studied. We examined several 60-100-m-deep canyons in semiarid northeastern Arizona, where rock type and structure are essentially constant, but where field data and a high-resolution digital elevation model reveal consistent morphologic and microclimatic differences between asymmetric north-and south-facing sideslopes. Cliffs account for 29% of the vertical relief of south-facing slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 63 publications
3
109
1
Order By: Relevance
“…For example, in central New Mexico, USA, decreased insolation on N-aspects appears to drive ecohydrologic feedbacks that increase vegetation cover and infiltration, ultimately inhibiting erosion and stabilizing N-aspects at steeper angles [Istanbulluoglu et al, 2008]. In northeastern Arizona, however, decreased insolation promotes gentler Naspects by increasing moisture persistence, which enhances the weathering of clay-cemented bedrock [Burnett et al, 2008]. In the unvegetated and poorly-consolidated Badlands of South Dakota, greater moisture retention on Nfacing slopes promotes saturation-related fluvial erosion [Churchill, 1981].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in central New Mexico, USA, decreased insolation on N-aspects appears to drive ecohydrologic feedbacks that increase vegetation cover and infiltration, ultimately inhibiting erosion and stabilizing N-aspects at steeper angles [Istanbulluoglu et al, 2008]. In northeastern Arizona, however, decreased insolation promotes gentler Naspects by increasing moisture persistence, which enhances the weathering of clay-cemented bedrock [Burnett et al, 2008]. In the unvegetated and poorly-consolidated Badlands of South Dakota, greater moisture retention on Nfacing slopes promotes saturation-related fluvial erosion [Churchill, 1981].…”
Section: Introductionmentioning
confidence: 99%
“…Drainage network development promotes asymmetry where competition for catchment area differs among hillslopes on opposite sides of a stream [Wende, 1995], and where basal streams preferentially undercut one aspect [Melton, 1960]. In topoclimatically-controlled models of HA development, the varying orientations of hillslopes relative to solar radiation and local wind patterns can alter moisture and energy balances, driving feedbacks that alter hydrologic processes, ecology, weathering, soil development and erosion among aspects [Hack and Goodlett, 1960;Churchill, 1981;Burnett et al, 2008;Istanbulluoglu et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Significant aspect related topoclimatic variability impacts both vegetation (e.g. type and density) and slope form (Burnett, 2004;Burnett et al, 2008). The study area slopes are too rugged to be grazed by livestock and we find no evidence for past livestock use on these slopes.…”
Section: Study Areamentioning
confidence: 62%
“…Both Churchill (1982) in Badland National Park (South Dakota, America) and Yair and Lavee (1980) in a badland (North Negev, Isreal) found that soil erosion intensity on the shady slopes is several orders of magnitude greater than that on the sunny slopes as a consequence of the higher antecedent moisture levels and erodible material on the shady slopes. In semi-arid northeastern Arizona, however, the northfacing bedrock slope is moist all year with weak clay expansion, leading to less cliff amount compared to that on south-facing slopes (Burnett et al 2008). Data from a Mediterranean burnt forest revealed that the sediment yields on south-facing plots are over 6 times higher than those on north-facing plots as a result of the denser plant cover and the thicker soil on the shady slopes (Marqués and Mora 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In the northern Ethiopian highlands, Van Den Eeckhaut et al (2009) also found that N-oriented slopes have a slightly higher landslide occurring frequency. Burnett et al (2008) demonstrated that aspect strongly influences slope and cliff processes through differences in soil moisture. However, these enumerative counts alone may fail to expose erosion intensity for the sunny and shady slopes.…”
Section: Slope Aspect and Wasting Mass Movementmentioning
confidence: 99%